Studi Pembuatan Cake Dengan Penambahan Kopi Arabika Dan Kopi Robusta - Esteria Priyanti; Shara Dyanti Ermyanda (Garina, 2022)
This research produces cake using arabica and robusta coffee. Hopefully, this processed cake will be accepted by coffee enthusiasts and the coffee shop industry so that coffee is not only known as a drink but can be processed into a sweet dessert. The aims of this study were 1) to determine the public's acceptance of cakes using arabica and robusta coffee; 2) to find out the ingredients formula in cake making that uses the best Arabica coffee and robusta coffee. The methods used in this study include experimental methods and hedonic tests. Data analysis used is descriptive analysis. The results showed that the products of arabica coffee cake and robusta coffee cake that were most liked and well received were products with a formula of 20% coffee addition. The formula for the best cake using arabica coffee and robusta coffee consists of 48 g of flour, 12 g of ground coffee, 13 g of powdered milk, 60 g of granulated sugar, 50 g of margarine, 30 g of butter, ¼ tsp of baking powder, and 2 chicken eggs. It can be concluded, the selected product can be an alternative to be processed into sweet desserts.